2018
DOI: 10.11646/zootaxa.4434.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Two new eriophyoid mites (Acari: Eriophyoidea) from West Bengal, India

Abstract: Two new species of eriophyoid mites viz. Abacarus sundarbanensis n. sp. infesting Pongamia glabra L. (Fabaceae) and Diptilomiopus augustifoliae n. sp. infesting Ambroma augusta (L.) (Sterculiaceae) respectively, are described from West Bengal, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Moreover, the genus Diptilomiopus were found in 7 samples (≈10% of total number of samples). So far, 83 Abacarus species were reported worldwide, among which 50 species infest plant family Poaceae (Amrine & Stasny 1994;Elhalawany & Ueckermann 2015;Elhalawany et al 2019;Elhalawany et al 2020;Laska et al 2018;Skoracka 2004;Sur et al 2018); most Abacarus species found in Guangxi University are also from Poaceae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the genus Diptilomiopus were found in 7 samples (≈10% of total number of samples). So far, 83 Abacarus species were reported worldwide, among which 50 species infest plant family Poaceae (Amrine & Stasny 1994;Elhalawany & Ueckermann 2015;Elhalawany et al 2019;Elhalawany et al 2020;Laska et al 2018;Skoracka 2004;Sur et al 2018); most Abacarus species found in Guangxi University are also from Poaceae.…”
Section: Introductionmentioning
confidence: 99%
“…2020; Laska et al . 2018; Skoracka 2004; Sur et al . 2018); most Abacarus species found in Guangxi University are also from Poaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Craemer et al (2005) confirmed this synonymy and transferred all additional 16 species described in Vilaia to Diptilomiopus. At present, 102 valid species of Diptilomiopus are known (Craemer et al, 2017;Sur et al, 2018;Amrine 2019, personal communication). So far 9 species of Diptilomiopus have been described on plants of the family Moraceae and 5 species on Anacardiaceae (Table 1).…”
Section: Introductionmentioning
confidence: 99%